2010
DOI: 10.1258/ebm.2010.010063
|View full text |Cite
|
Sign up to set email alerts
|

Cell line models for differentiation: preadipocytes and adipocytes

Abstract: In vitro models have been invaluable in determining the mechanisms involved in adipocyte proliferation, differentiation, adipokine secretion and gene/protein expression. The cells presently available for research purposes all have unique advantages and disadvantages that one should be aware of when selecting cells. Established cell lines, such as 3T3-L1 cells, are easier and less costly to use than freshly isolated cells, even though freshly isolated cells allow for various comparisons such as the in vitro eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
219
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(221 citation statements)
references
References 69 publications
1
219
1
Order By: Relevance
“…Taken together, leptin acts in an autocrine/paracrine manner via the PI3K/Akt signaling pathway, contributing to sustain adipocyte inflammation through the synthesis and release of the alarmin TNC. Data are based on the immortalized cell line 3T3-L1 since the preadipose cell line 3T3-L1 is one of the most common in vitro models used in the study of adipocyte biology due to its potential to differentiate from fibroblasts to adipocytes 58 . However, 3T3-L1 adipocytes display features of multiple adipocyte lineages, and this should be taken into consideration when interpreting data from experiments using this cell line 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, leptin acts in an autocrine/paracrine manner via the PI3K/Akt signaling pathway, contributing to sustain adipocyte inflammation through the synthesis and release of the alarmin TNC. Data are based on the immortalized cell line 3T3-L1 since the preadipose cell line 3T3-L1 is one of the most common in vitro models used in the study of adipocyte biology due to its potential to differentiate from fibroblasts to adipocytes 58 . However, 3T3-L1 adipocytes display features of multiple adipocyte lineages, and this should be taken into consideration when interpreting data from experiments using this cell line 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Adipogenesis is the process by which preadipocytes differentiate into mature adipocytes. Preadipocyte proliferation and differentiation have been widely studied with a well-characterized and reliable in vitro model using the 3T3-L1 preadipocyte cell line, which was isolated from Swiss 3T3 mouse embryos (Green & Meuth 1974;Poulos et al 2010). In this study, we investigated the effects of porcine PID1 on 3T3-L1 preadipocyte proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient (isolatable) adipose tissue is present in all adipose depots of cattle for cell isolation and comparative evaluation (Dodson et al, 2010b) and a broadening database of research tools is rapidly being developed for bovine adipose research models. Furthermore, previous studies have indicated that the physiology of adipocytes derived from cattle may be different from other well-understood adipocyte models (such as 3T3-L1) (Fernyhough et al, 2007;Taniguchi et al, 2008a,b;Dodson et al, 2010a,c;Poulos et al, 2010). Bovine adipocytes with potential dominance are the cell model of studying adipogenesis and lipid metabolism for improving animal production and serving human health.…”
Section: Introductionmentioning
confidence: 99%